Avaliação da responsabilidade social corporativa: estudo nas empresas brasileiras de energia elétrica - Leal, Paulo Henrique (2016)
Corporate social responsibility is considered by many authors as essential to continuity issues and competitiveness of the company; while the evaluation of the returns generated by corporate social responsibility is considered important in business context. Thus, this study aims to investigate the relationship of the level of corporate social responsibility with variable of internal and external characteristics of the company. For this, was carried an exploratory, bibliographical and documentary research and analyzed sustainability reports and financial statements of the companies. In addition, were used statistical techniques of descriptive analysis to investigate the evaluation of corporate social responsibility to stakeholders, and regression with panel data to verify the relationship of corporate social responsibility level with the variable participation in the ISE, company size and profitability of the company over the five years of research. The study sample comprised 16 Brazilian electric companies regulated by ANEEL, and was considered a period of five years, from 2010 to 2014. The results of descriptive analysis indicate that the public in general stakeholders presented the highest mean of evaluation corporate social responsibility and customers had the lowest mean evaluation of corporate social responsibility, suggesting that corporate social responsibility provides more economic and social returns to the general public and less economic returns for customers. The regression model with panel data showed that there is a positive and significant relationship between the level of corporate social responsibility and the size of the company. In relation to variable participation in the ISE and profitability of the company there was not significant relationship, It can not be inferred that the participants of the ISE companies, or companies with more profitability tend to have a higher level of corporate social responsibility. It was concluded that corporate social responsibility provided various economic and social returns to most stakeholders investigated and that there is progress over the years in the returns provided for some of those related to public company. In addition, positive relationship between corporate social responsibility level with the size of the company was seen, suggesting that larger companies tend to present higher level of corporate social responsibility.